Glad to be here: Lessons in high performance from the Blue Angels. Issue 67 (14th December 2012) - Foley, John
Abstract: Foley, the former lead solo pilot of the Navy's elite Blue Angels shares their process and mind‐set for achieving the highest level of performance. It starts with the "Glad to Be Here" mind‐set, which underpins the Diamond Performance Framework. This is built around tactical or strategic CenterPoints. A high belief level is necessary for high achievement, and with this comes clarity of vision. Delivery of a brief, which "contains the relevant details that people need before they get started, " helps people know what is expected. Commitment is based on contracts, and after‐action debriefs are necessary, for "celebrating your victories and sharing your gratitude."